A struggle of civilization against barbarism: about universities as autonomous zones. (1st October 2016) - Drainville, André C.
Abstract : This paper takes a longue durée look at universities at the core of the world economy, where the modern idea of intellectuals as trustees of the reflexive structures of society has achieved its most enduring institutional form. To wrest thinking away from a conformism that makes us see universities as nothing more than organisations amongst organisations forever in process of adapting themselves to the exigencies of world ordering, we focus on three moments of rupture: (i) the 'prehistory of higher education', when the work of the medieval renaissance was 'largely done' and original universities where founded in the folds of the nascent European économie-monde, (ii) the crisis of the Bretton Woods world order, and (iii) the present juncture